INCOME OF BUSINESS ENTITIES: ECONOMIC ESSENCE AND CLASSIFICATION - KOZACHENKO, ANNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article highlights the views of scholars on the economic meaning of the concept of "income". It is determined that the term "income" should be considered an economic category, which means the direct receipt of certain assets (material resources or money) or a decrease in liabilities that lead to an increase in equity (minus the increase in equity contributions from owners or participants). The study of the concept of "income" in a broad interpretation from an economic and accounting point of view made it possible to establish the following properties:   1) income - is a type of financial results of economic activity for a certain period; 2) characterizes the economic benefits; 3) the main forms of economic benefits - is the proceeds from the sale of other property, from non-operating transactions; 4) economic benefits that generate income are estimated by their amount in cash. An analysis of the scientific literature on the identification of the definitions of "profit", "income" and "revenue", which gave reason to believe that the views of modern economists are divided into two categories, some scientists who equate income with sales revenue, others - recognize income in a broader category and note its impact on determining the performance of the entity and the amount of equity. The incomes of the enterprise which can be both in money, and not in monetary forms are considered. For effective revenue management, it is advisable to have a scientifically sound and detailed classification according to certain characteristics for the purposes of accounting, analysis, planning and auditing. It is determined that both foreign and domestic scientific sources reflect certain elements of income classifications that have more theoretical than practical significance. Thus, the classification features of enterprise income can be those characteristics that clearly identify the sources of their formation, factors of influence, time and method of recognition, place of formation
Keywords: income; revenue; profit; classification features; components